Features of ionic transport processes in a model of arterial hypertension - A. V. Nosarev; Yu. G. Birulina; I. V. Petrova; I. V. Kovalev; S. V. Gusakova; L. V. Smagliy; E. S. Teslya; A. Yu. Shamanaev; E. V. Pushkina; M. A. Medvedev (Бюллетень сибирской медицины)
Aim. To study the ionic mechanisms which underlie regulation contractile activity of vascular smooth muscles and the erythrocytes membrane potential from spontaneously hypertensive rats.Materials and methods. The effect of acetylcholine (ACX), 10 μM, and Ca2+ -ionophore A23187, 10 μM, on the contractile reactions of isolated smooth muscle segments of the aorta from 11-week-old spontaneously hypertensive rats (SHR) and Wistar – Kyoto rats (WKY) induced by phenylephrine (PE), 1 μM, was measured by the mechanography. 11-week-old SHR were divided into control and experimental groups depending on the drug administration (amlodipine 10 mg/kg given intragastrically). Blood pressure (BP) in SHR was measured before and after treatment. The amplitude of the hyperpolarizating response (HO) and the activity of Ca2+-dependent K+-channels of the erythrocyte membrane of SHR were performed with potentiometric method.Results. In response to the stimulating effect of the ACX or the calcium ionophore A23187, the smooth muscle segments of the aorta from the WKY and SHR precontracted with PE were relaxed. To the addition of the ACX, the vascular segments of the SHR responded with a stronger dilatation than the WKY segments, but not the action of the Ca2+-ionophore. Treatment of SHR with blocker of Ca2+-channels of L-type amlodipine caused a decrease the BP, and an increase in the relaxing effect of intact aortic segments on the ACX and Ca2+-ionophore. There was an increase the amplitude of HO and activity of Ca2+-dependent K+-channels of the erythrocyte membrane from SHR.Conclusion. Relaxation of vascular smooth muscle in SHR is caused by changes in the endothelial function and Ca2+-dependent ionic conductivity of the myocyte membrane. An increase of the hyperpolarizating response of the erythrocyte membrane from rats with spontaneous hypertension is associated with activation of potassium channels. The selective effect on these intracellular targets can serve as a basis for the development of antihypertensive drugs.